Transient analysis of a queue with queue-length dependent MAP and its application to SS7 network. (1999) - Choi, Bong Dae; Choi, Sung Ho; Sung, Dan Keun; Lee, Tae-Hee; Song, Kyu-Seog
Abstract : We analyze the transient behavior of a Markovian arrival queue with congestion control based on a double of thresholds, where the arrival process is a queue-length dependent Markovian arrival process. We consider Markov chain embedded at arrival epochs and derive the one-step transition probabilities. From these results, we obtain the mean delay and the loss probability of the n th arrival packet. Before we study this complex model, first we give a transient analysis of an MAP / M / 1 queueing system without congestion control at arrival epochs. We apply our result to a signaling system No. 7 network with a congestion control based on thresholds.